Standard guidelines for the publication of telomere qPCR results in evolutionary ecology. (24th March 2020) - Morinha, Francisco; Magalhães, Paula; Blanco, Guillermo
Abstract: Telomere length has been used as a proxy of fitness, aging and lifespan in vertebrates. In the last decade, dozens of articles reporting on telomere dynamics in the fields of ecology and evolution have been published for a wide range of taxa. With this growing interest, it is necessary to ensure the accuracy and reproducibility of telomere length measurement techniques. Real‐time quantitative PCR (qPCR) is routinely applied to measure relative telomere length. However, this technique is highly sensitive to several methodological variables and the optimization of qPCR telomere assays remains highly variable between studies. Therefore, standardized guidelines are required to enable the optimization of robust protocols, and to help in judging the validity of the presented results. This review provides an overview of preanalytical and analytical factors that can lead to qPCR inconsistencies and biases, including: (a) sample type, collection and storage; (b) DNA extraction, storage and quality; (c) qPCR primers, laboratory reagents, and assay conditions; and (d) data analysis. We propose a minimum level of information for publication of qPCR telomere assays in evolutionary ecology considering the methodological pitfalls and sources of error. This review highlights the complexity of the optimization and validation of qPCR for telomere measurement per se, demonstrating the importance of transparency and clarity of reporting methodological details required for reliable, reproducible and comparable qPCR telomere assays. We encourage efforts to implement standardized protocols that ensure the rigour and quality of telomere dynamics studies.